Electroless nickel plating on a biomineral-based sponge structure. Issue 2 (6th December 2021) - Takeoka, Hiroaki; Seike, Musashi; Nakamura, Yoshinobu; Imai, Hiroaki; Oaki, Yuya; Fujii, Syuji
Abstract : A 3-dimensional porous material prepared by transferring a sponge structure of a biomineral is coated by nickel via aqueous electroless plating. Abstract : A 3-dimensional polypyrrole–palladium nanocomposite material was prepared by transferring a sponge structure of a sea urchin spine via chemical oxidative polymerization. The nanocomposite material was successfully coated with nickel, maintaining the 3-dimensional sponge structure by electroless plating in an aqueous medium.